La santé sexuelle et reproductive en Tunisie. Institutions médicales, lois et itinéraires thérapeutiques des femmes après la révolution - Irene Maffi; Malika Affes (L’Année du Maghreb)
In this article, written in the form of an interview, Malika Affes, midwife in charge of one of the family planning units of La Rabta Hospital in Tunis, and Irene Maffi, anthropologist, discuss sexual and reproductive health in Tunisia. Their conversation - which is the result of a 10-month collaboration - tackles different topics related to the institutions in charge of sexual and reproductive health, the laws regulating the access to these services, the therapeutic itineraries of women and the attitudes of health care providers. The authors particularly explore the local representations of the female body, the socioeconomic profiles of women using government sexual and reproductive health clinics, the knowledge of the law among patients and health practitioners, the application of sexual and reproductive rights in Tunisia, the impact of the revolution of 2011 and of the economic crisis on the public health services, men’s involvement in sexual and reproductive practices.